Encouraging Cross-Disciplinary Collaboration and Innovation in Epidemiology in Japan - Yokomichi, Hiroshi; Mochizuki, Mie; Yamagata, Zentaro (Frontiers in Public Health, 2021)
Background: Scientific innovation is often achieved through the intersection of ideas from different fields. However, barriers prevent non-epidemiologists from cultivating interests in epidemiology or undertaking epidemiologic work. In this study, we evaluated changes in the diversity of research topics in an epidemiologic journal over time. We aimed to understand how epidemiologists and non-epidemiologists communicate about epidemiologic data and how this impacts innovation in the field. Methods: We categorized the topics of articles published in the Journal of Epidemiology during the early and late 2010s based on their titles. We calculated the Shannon–Weaver diversity index (H′) to measure changes in the diversity of topics addressed by published articles. Results: Comparing 2011–2013 with 2017–2019, there was no significant change in the diversity of article topics (H′ = 4.25 and 4.21, respectively) published in the Journal of Epidemiology. Conclusion: To encourage healthcare providers and public administrators to conduct or comment on epidemiologic studies, epidemiologists should present their findings in easily understood language with appropriate and relevant statistical indicators and useful illustrations. Bringing experience from other specialties into epidemiology may yield new findings from epidemiologic data because of the exposure of non-epidemiologists to different values, workplaces, and occupations. Collaboration among professionals from varied backgrounds and with varied occupational experiences may help to promote scientific innovation by broadening perspectives. In addition, a range of professional experiences may enable individuals to solve difficult research questions more easily by themselves.